Suppression of Methamphetamine Self-Administration by Ketamine Pre-treatment Is Absent in the Methylazoxymethanol (MAM) Rat Model of Schizophrenia - Ruda-Kucerova, Jana; Babinska, Zuzana; Stark, Tibor; Micale, Vincenzo (Neurotoxicity research, 2017)
Ketamine may prove to be a potential candidate in treating the widespread drug addiction/substance abuse epidemic among patients with schizophrenia. Clinical studies have shown ketamine to reduce cocaine and heroin cravings. However, the use of ketamine remains controversial as it may exacerbate the symptoms of schizophrenia. Therefore, the aim of this study is to characterize the effects of ketamine on drug addiction in schizophrenia using the methylazoxymethanol (MAM) acetate rat model on operant IV methamphetamine (METH) self-administration. MAM was administered intraperitoneally (22 mg/kg) on gestational day 17. Locomotor activity test and later IV self-administration (IVSA) were then performed in the male offspring followed by a period of forced abstinence and relapse of METH taking. After reaching stable intakes in the relapse phase, ketamine (5 mg/kg) was administered intraperitoneally 30 min prior to the self-administration session. As documented previously, the MAM rats showed a lack of habituation in the locomotor activity test but developed stable maintenance of METH self-administration with no difference in operant behaviour to control animals. Results show that ketamine treatment significantly reduced the METH intake in the control animals but not in MAM animals. Ketamine effect on METH self-administration may be explained by increased glutamatergic signalling in the prefrontal cortex caused by the N-methyl-D-aspartate antagonism and disinhibition of GABA interneurons which was shown to be impaired in the MAM rats. This mechanism may at least partly explain the clinically proven anti-craving potential of ketamine and allow development of more specific anti-craving medications with fewer risks.
Keywords: Ketamine; MAM model; lokomoce; operantní podmiňování; Dose-Response Relationship, Drug; ketamin; schizofrenie; analýza rozptylu; Female; Sprague-Dawley rats; Analysis of Variance; krysa rodu Rattus; Self Administration; Schizophrenia; zvířata; stimulanty centrálního nervového systému; Self-administration; methamfetamin; autoaplikace; potkani Sprague-Dawley; ženské pohlaví; methylazoxymethanolacetát; Methylazoxymethanol Acetate; Rats; Conditioning, Operant; Locomotion; vztah mezi dávkou a účinkem léčiva; Rats, Sprague-Dawley; Animals; Central Nervous System Stimulants; Disease Models, Animal; Methamphetamine; modely nemocí na zvířatech